Isomer selective ion-exchange intercalation of nitrophenolates into the layered double hydroxide [LiAl2(OH)(6)]Cl center dot xH(2)O - Ragavan, A; Khan, A; O'Hare, D (2006)
The anions 4-nitrophenolate (4-NP) and 2,4-dinitrophenolate (2,4-DNP) undergo anion-exchange intercalation with [LiAl2(OH) 6]Cl·xH2O, ([Li-Al-Cl] LDH), to yield the fully exchanged intercalates [LiAl2(OH)6]{4-NP}·2H 2O and [LiAl2(OH)6]{2,4-DNP}·H 2O respectively. 4-NP can be selectively intercalated in [Li-Al-Cl] LDH from an equimolar mixture of 2-nitrophenolate (2-NP), 3-nitrophenolate (3-NP) and 4-nitrophenolate (4-NP). Intercalation of 2,4-DNP is competitive with intercalation of 4-NP into [Li-Al-Cl] LDH from an equimolar solution of the two NPs. The observed intercalation preferences of these two NPs is found to be dependent on both temperature and solvent. 2,4-DNP is selectively intercalated into [Li-Al-Cl] LDH compared to 4-NP at high temperature and in polar solvents. The kinetics of intercalation of 4-NP and 2,4-DNP into [Li-Al-Cl] LDH has been studied using time-resolved in situ energy dispersive X-ray powder diffraction (EDXRD). The rate of intercalation of 4-NP is faster that of 2,4-DNP, but 2,4-DNP is thermodynamically preferred by [Li-Al-Cl] LDH. © The Royal Society of Chemistry 2006.